Integrating Task-Based Blended Learning Approach in Teaching Public Speaking - Hafizoah, Kassim; Nik Aloesnita, Nik Mohd Alwi; Zailin Shah, Yusoff; Ainol Haryati, Ibrahim (2016)
Public speaking is a sustained formal presentation made to an audience. For the English as a Second Language (ESL) learners, practice enables them to identify and address speech-related concerns prior to delivery. As such, it is highly encouraged for the students to engage in practice to promote skills training. In skills training for public speaking, the speech planning process is divided into specific skills that can be mastered, first, in isolation, and then together. Task-based instruction is an ideal tool for implementing the principle of skills training especially with the use of technology. Thus, there is potential for employing task-based approach for public speaking in a blended learning environment.